Isolation of total rna at early stage of jatropha seeds development - Sem, Poh Lian (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Jatropha curcas is an oil-bearing shrub and has great potential for development as a biofuel crop. Genetic engineering technology is being adopted to improve the production and quality of the biofuel. J. curcas seed is rich in fatty acid, storage protein, polysaccharides and other secondary metabolites which make isolation of total RNA to be difficult. The aim for this study is to generate an effective protocol which able to isolate good quality of total RNA from early stage of Jatropha seeds that is very important for many gene expression studies. The described methods were CTAB-LiCl method I, CTAB-LiCl II and CTAB-isopropanol method. Compare to these three methods, CTAB-LiCl method II was the preferred method. This method was able to yield up to 0.239 μg/μl of RNA with the A260/A280 and A260/A230 ratio ranged from 1.8 - 2.0 and 0.619 - 1.248, respectively. This indicated total RNA free of protein contamination while slight contaminated with organic compound. Using the CTAB-LiCl method II, RNA was successfully obtained from Jatropha seeds.